Actions speak louder than words: psychosocial effect (PE) on work for spiritual management technology - Mohd. Syukri Yeoh Abdullah; Ahmad Kilani Mohamed; Rusdi Abd Rashid; Mohammad Hannan Mia; Irwan Mohd Subri (American Society For Engineering Education, 2024)
Vol. 6, Special Issue